Spherical Aberration of Point Spread Function with Asymmetric Pupil Mask. (29th November 2016) - Andra, Naresh Kumar Reddy; Dasari, Karuna Sagar
Abstract : Point spread function underneath spherical wave aberration with antiphase apodization has been obtained by one-dimensional pupil mask functions. In the presence of spherical aberration, suppression of optical side-lobes has increased on one side of the point spread function with the width of the periphery strips within the pupil mask. On introducing wave aberration effect, there exists dependence of the lateral resolution of central peak of the asymmetric point spread function on the amount of amplitude masking. However, the magnitude of intensity of central peak is originated be to amplified by the highest degree of amplitude and phase masking. Additionally, for aberrated asymmetric PSF, FWHM increases and it further decreases with the control parameters of amplitude and phase mask. The magnitude of this corollary can quantify the super resolution of diffracted structures under spherical aberration.